Heavy metals in the sediments of Laoshan Bay, China: Distribution and contamination assessment. (December 2022) - Tian, Xu; Xu, Weikun; Wang, Fuqiang; Ye, Youquan; Liu, Ming; Shi, Honghua; Fan, Dejiang; Xu, Fangjian
Abstract: We analyzed total organic carbon (TOC), total nitrogen (TN), and heavy metals in 58 sediment samples from the Laoshan Bay, China. TOC and TN results identified marine primary production as the dominant source for organic matter, and the weak correlations between TOC, TN, and heavy metals indicated the terrestrial origin of heavy metals. Cd showed insignificant correlations with other metals, which suggests that agriculture production is the main anthropogenic activity affecting the distribution of Cd. Pb contamination in past 50 years was likely to have occurred because of fossil fuel combustion. Despite 210 Pb dating, it was still difficult to trace the contamination condition over interannual variations. Nonetheless, these results provide data for monitoring Pb contamination. As Laoshan Bay is an important economic area, it would be beneficial to conduct further studies to determine the sources and degree of contamination for each heavy metal. Highlights: Heavy metal distribution and contamination were assessed in Laoshan Bay, China. Heavy metals were mainly sourced from land. Low Igeo values for some elements indicated their origin from natural sources. High EF and Igeo values of Pb suggested indicated its anthropogenic origin.